Ontogeny-driven rDNA rearrangement, methylation, and transcription, and paternal influence. - Yih-Horng Shiao; Robert M Leighty; Cuiju Wang; Xin Ge; Erik B Crawford; Joshua M Spurrier; Sean D McCann; Janet R Fields; Laura Fornwald; Lisa Riffle; Craig Driver; Octavio A Quiñones; et al. (PLoS ONE)
Gene rearrangement occurs during development in some cell types and this genome dynamics is modulated by intrinsic and extrinsic factors, including growth stimulants and nutrients. This raises a possibility that such structural change in the genome and its subsequent epigenetic modifications may also take place during mammalian ontogeny, a process undergoing finely orchestrated cell division and differentiation. We tested this hypothesis by comparing single nucleotide polymorphism-defined haplotype frequencies and DNA methylation of the rDNA multicopy gene between two mouse ontogenic stages and among three adult tissues of individual mice. Possible influences to the genetic and epigenetic dynamics by paternal exposures were also examined for Cr(III) and acid saline extrinsic factors. Variables derived from litters, individuals, and duplicate assays in large mouse populations were examined using linear mixed-effects model. We report here that active rDNA rearrangement, represented by changes of haplotype frequencies, arises during ontogenic progression from day 8 embryos to 6-week adult mice as well as in different tissue lineages and is modifiable by paternal exposures. The rDNA methylation levels were also altered in concordance with this ontogenic progression and were associated with rDNA haplotypes. Sperm showed highest level of methylation, followed by lungs and livers, and preferentially selected haplotypes that are positively associated with methylation. Livers, maintaining lower levels of rDNA methylation compared with lungs, expressed more rRNA transcript. In vitro transcription demonstrated haplotype-dependent rRNA expression. Thus, the genome is also dynamic during mammalian ontogeny and its rearrangement may trigger epigenetic changes and subsequent transcriptional controls, that are further influenced by paternal exposures.